Romanticism’s Scattered Leaves - Stauffer, Andrew (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractThis essay considers the archival anxieties attending the reproduction, reception and preservation of material remains, in the Romantic period and in our own. I focus on the recurrent trope of scattered leaves as an index of Romantic concerns about the fates of works on paper in the age of industrial papermaking. I suggest that the consequent transformation of the archive in the nineteenth century, both as a concept and as a set of material practices, offers a window onto our current moment of digital transformations of the Romantic legacy. The Romantic archive is haunted by the ruins of paper, unsettled by the changing forms of information storage and retrieval that characterize its day and ours. Ultimately, I argue that the goal of the digital archive should be to send us back to the paper legacies of the Romantics, not to wean us away from those material forms.